Can training in advanced clinical skills in obstetrics, neonatal care and leadership, of non-physician clinicians in Malawi impact on clinical services improvements (the ETATMBA project): a process evaluation. Issue 8 (12th August 2014) - Ellard, David R; Chimwaza, Wanangwa; Davies, David; O'Hare, Joseph Paul; Kamwendo, Francis; Quenby, Siobhan; Griffiths, Frances
Abstract : Objectives: The 'enhancing human resources and the use of appropriate technologies for maternal and perinatal survival in sub-Saharan Africa' (ETATMBA) project is training emergency obstetric and new-born care (EmONC) non-physician clinicians (NPCs) as advanced clinical leaders. Our objectives were to evaluate the implementation and changes to practice. Design: A mixed methods process evaluation with the predominate methodology being qualitative. Setting: Rural and urban hospitals in 8 of the 14 districts of northern and central Malawi. Participants: 54 EmONC NPCs with 3 years' plus experience. Intervention: Training designed and delivered by clinicians from the UK and Malawi; it is a 2-year plus package of training (classroom, mentorship and assignments). Results: We conducted 79 trainee interviews over three time points during the training, as well as a convenience sample of 10 colleagues, 7 district officers and 2 UK obstetricians. Trainees worked in a context of substantial variation in the rates of maternal and neonatal deaths between districts. Training reached trainees working across the target regions. For 46 trainees (8 dropped out of the course), dose delivered in terms of attendance was high and all 46 spent time working alongside an obstetrician. In early interviews trainees recalled course content unprompted indicating training had been received. Colleagues and district officers reported cascading of knowledge and initial changes in practice indicating early implementation. By asking trainees to describe actual cases we found they had implemented new knowledge and skills. These included life-saving interventions for postpartum haemorrhage and eclampsia. Trainees identified the leadership training as enabling them to confidently change their own practice and initiate change in their health facility. Conclusions: This process evaluation suggests that trainees have made positive changes in their practice. Clear impacts on maternal and perinatal mortality are yet to be elucidated.